1975
DOI: 10.1577/1548-8659(1975)104<762:teotot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature on the Development and Survival of the Eggs and Larvae of the Atlantic Silverside, Menidia menidia

Abstract: Eggs of Atlantic silverside, Menidia menidia, were fertilized and incubated at 15, 17, 20, 25 and 30 C. The times to hatching at each temperature were 27.0, 12.4, 9.8, 4.8 and 3.0 days respectively. Thermal shocks of +8 C produced 0% mortality for larvae reared at 17 and 20 C, 19% for larvae reared at 25 C, and 11% for larvae reared at 30 C. Thermal shocks of q-•[4 C produced 3% mortality for larvae reared at 17 C, 0% for larvae reared at 20 C, and 100% for larvae reared at 25 and 30 C. Since the larvae of Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This article provides the first detailed report of the field ecology of Atlantic silverside larvae, although laboratory studies on this larval species have been conducted for decades (e.g., Austin et al, 1975;Middaugh and Lempesis, 1976;Morgan and Prince, 1977;Deacutis, 1978;Bengtson, 1985;Lankford et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This article provides the first detailed report of the field ecology of Atlantic silverside larvae, although laboratory studies on this larval species have been conducted for decades (e.g., Austin et al, 1975;Middaugh and Lempesis, 1976;Morgan and Prince, 1977;Deacutis, 1978;Bengtson, 1985;Lankford et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…According to the regression coefficients in the age-length equations, the larvae in our study grew at 0.65-0.66 mm/d. Barkman et al (1981) found that over a length range of about 12-90 mm TL Atlantic silverside grew at 0.84 mm/d, on the basis of an age-length relationship determined with otolith analysis, whereas Mulkana (1966) estimated a growth rate of 7-11 mm/month (0.23-0.37 mm/d) on the basis of length-frequency analyses of a cohort. Volson (2012) found that larval length at hatching was significantly greater for Atlantic silverside larvae in the UPJP than for larvae in the UPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups of tens to hundreds of adults spawn clusters of thousands of eggs on shallow water vegetation (Conover & Kynard 1984). Eggs take roughly 1 week to hatch at 21°C, but this incubation period is negatively correlated with water temperate (Austin, Sosnow & Hickey 1975). After hatching, the larvae and juveniles grow quickly and reach adult size prior to offshore migration in the fall; over-winter survival is highly size-dependent (Conover & Murawski 1982;Conover & Present 1990;Munch, Mangel & Conover 2003).…”
Section: Study Speciesmentioning
confidence: 99%
“…For example, direct variations in lunar light intensity, from illumination as low as 1.25 × 10 −5 μ E m −2 s −1 (new moon or starlight) to 2.99 × 10 −3 μ E m −2 s −1 (zenith of full moon), are postulated to cause shifts in lunar rhythms in the spawning of marine organisms on a global basis, including echinoids ( Diadema spp. [ Muthiga , 2003; Coppard and Campbell , 2005]), annelids (palolo worms [ Caspers , 1984; Olive et al , 2005]), and fish [ Austin et al , 1975; Gladstone , 2007; Pisingan and Takemura , 2007].…”
Section: Introductionmentioning
confidence: 99%